EXPLORATION AND IDENTIFICATION OF THE ENTOMOPATHOGENIC FLOW OF Beauveria bassiana USING THE BAITING METHOD - Fiza Intan Nur Oktaviani; Inayah Fitri (Jurnal Matematika dan Sains (JMS), 2021)
Control of plant pests by using biological agents is one way to create higher quality plants. One of the biological agents used to control pests and plant diseases is microorganisms. Specific pest control, cheap, also has a lower risk of environmental pollution. Entomopathogenic fungi are organisms that live as insect parasites, fungi, including microorganisms that generally live in the soil. Soil is one of the places to see the presence of fungi in nature. One of the entomopathogenic fungi that has the potential to control several species of insect pests is Beauveria bassiana. This fungus is very effective as a biological agent that can infect insect pests such as the Lepidoptera order. The fungus Beauveria bassiana is a microscopic fungi with somatic structures that form fine thread hyphae (septal hyphae). Entomopathogenic fungi can be obtained by exploration from various locations with the insect feeding system method. Fungus isolates can also be obtained through the insect bait method.